Combining between rhetoric and poetry at the Gahleon and its impact on poetry - Qadera, Ghaithaa; Nzeha, Basel (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with the phenomenon of combining rhetoric and poetry at a number of the Gahleon, and the statement of the effect of this combining in their poetry, explaining through the issue of conflict of prestige betweenthe orator and the poet in pre-Islamic era, and how this conflict has been compromised between who combined the technocracy, as the research shows the reason oflack of those who gathered between technocracy. The effect of combining in poetry is dealt with research on two levels: the stylistic level, and shows all forms of repetition: repeating letters, words and methods. While appears in the substantive level (moral): the pursuit of incomprehensible, the concentration on thinking and subjects, and the large number of wisdom and wills.